Circulating Heat Shock Protein 70 in Health, Aging and Disease - Njemini, Rose (BioMed Central, 2011)
BACKGROUND: Heat shock proteins (Hsp) are ubiquitously synthesised in virtually all species and it is hypothesised that they might have beneficial health effects. Recent studies have identified circulating Hsp as an important mediator in inflammation - the effects of low-grade inflammation in the aging process are overwhelming. While much is known about intracellular Hsp70, scant data exist on circulating Hsp70 in the aging context. Therefore, the objectives of this study were to investigate the effect of age and disease on circulating Hsp70 and, in particular, to evaluate the association between circulating Hsp70 and inflammatory parameters. RESULTS: Serum Hsp70, Interleukin (IL) -10, IL-6 and Tumor Necrosis Factor (TNF) alpha concentrations were determined in 90 hospitalised geriatric patients (aged 83 ± 6 years) and in 200 community-dwelling control subjects (100 elderly, aged 74 ± 5 years, and 100 young, aged 23 ± 3 years). In the community-dwelling elderly, serum Hsp70 and IL-10 concentrations were significantly lower and IL-6 was significantly higher when compared to healthy young control subjects. Elderly patients presenting inflammation (CRP serum levels ≥5 mg/L) showed significantly (p = 0.007) higher Hsp70 values; and Hsp70 correlated positively (p < 0.001) with IL-6 and CRP, but not with TNF-alpha or IL-10. A significant association was also noted between Hsp70 levels and the degree of dependency and cognitive decline in geriatric patients. CONCLUSIONS: The present data provide new evidence that serum concentration of Hsp70 decreases with age in a normal population. Our study also shows that higher levels of Hsp70 are associated with inflammation and frailty in elderly patients.